Gambaran Infertilitas Pada Wanita Berdasarkan Status Follicle Stimulating Hormone (FSH) dan Luteinizing Hormone (LH) Rskia Sadewa - Salzabilla Poha; Farida Noor Irfani; Arif Bimantara (Universitas Malahayati Lampung, 2025)
ABSTRACT Infertility is a complex condition that can be caused by various factors, including imbalances in reproductive hormones such as Follicle-Stimulating Hormone (FSH) and Luteinizing Hormone (LH). To describe infertility in women based on FSH and LH hormone levels at RSKIA Sadewa. This study used a descriptive quantitative method with secondary data obtained from the medical records of infertile female patients at RSKIA Sadewa during the period of July 2024 to June 2025. Data were analyzed univariately and Chi-square using SPSS. Examinations for infertility were most commonly performed in women aged 26–35 years. Abnormal levels of FSH and LH were more frequently observed in age groups 25 years and 35 years. Chi-square test showed no significant association between age and FSH levels (p=0.371) or LH levels (p=0.377). There is no significant association between FSH and LH levels and age in infertile women. Infertility is multifactorial, influenced not only by hormonal levels but also by other factors beyond the reproductive hormonal system. Keywords: Infertility, FSH Hormone, LH Hormone, Female Reproduction ABSTRAK Infertilitas merupakan permasalahan kompleks yang dapat disebabkan oleh berbagai faktor, termasuk ketidakseimbangan hormon reproduksi seperti Folliclestimulating Hormone (FSH) dan Luteinizing Hormone (LH).Mengetahui gambaran infertilitas pada wanita berdasarkan kadar hormon FSH dan LH di RSKIA Sadewa. Penelitian ini menggunakan metode deskriptif kuantitatif dengan data sekunder dari rekam medis pasien wanita infertil di RSKIA Sadewa periode Juli 2024–Juni 2025. Data dianalisis secara univariat dan uji Chi-square menggunakan SPSS.Pemeriksaan infertilitas paling banyak ditemukan pada wanita usia 26–35 tahun. Abnormalitas kadar FSH dan LH lebih sering terjadi pada kelompok usia 25 tahun dan 35 tahun. Uji Chi-square menunjukkan tidak ada hubungan signifikan antara usia dengan kadar FSH (p=0,371) maupun LH (p=0,377). Tidak terdapat hubungan signifikan antara kadar FSH dan LH dengan usia pada wanita infertil. Infertilitas bersifat multifaktorial, tidak hanya dipengaruhi kadar hormon, tetapi juga faktor lain di luar sistem hormonal. Kata kunci: Infertilitas, Hormon FSH, Hormon LH, Reproduksi Wanita